Estimation of climatic parameters from solar indices using ground based data from Kenya, East Africa (Journal of Science and Technology, 2016)
The daily meteorological data of relative humidity, maximum, minimum, and average temperatures obtained from five stations of the Kenya Meteorological Department over the period 1986 to 2005 were filtered and reduced to monthly means. Monthly data of solar indices: Sunspot number, F10.7 cm solar radio flux and Mg II core-to-wing ratio covering the same period wereemployed to model the meteorological variables using the linear multivariate model and applying least square fittings. Validity of the models was tested using Mean Bias Error (MBE) and Root Mean Square Error (RMSE) statistical indicators. The correlations between the observed and predicted values from the models were significant at above 95% level of confidence. The modelsshow the effect of solar forcing on the climatic parametErs at different locations in Kenya. Solar forcing of climate is evident in Kenya.